Centro de Documentação Indígena dos Missionários da Consolata : o processo de construção de um espaço memorial para os povos indígenas de Roraima - Cunha, Marcos Maciel Lima (2019)
This work is the result of a research developed in the archive of the Missionaries of the Consolata in Roraima, called the Indigenous Documentation Center (CDI), in operation since 2012. The work seeks to reflect on the construction of a space of historical nature aimed at aggregating values and knowledge reflecting on the role of the missionaries in this new project aimed at the valorization of materials on indigenous peoples and trajectory Of these in the fight for the recognition of their lands. It is known that the historical process about the indigenous movement has lasted decades and many records of these moments are stored in this collection. And it is thinking of preserving these documents that the CDI has been materiating as the newest project, which I consider to be, not only important for the history of the indigenous movement, but also a historical memory of the missionary presence in Roraima. The work will serve as subsidies to understand how the CDI acquis is organized and the attributions of this space, with regard to the safeguarding of the documentary heritage of the state. It is also the report of work experience that I have been developing with the collection of the Consolata Institute, in organizing and cataloging the documentation here, as well as a historical account of the life trajectory of its founder and creator.